ngonhuminh
14 tháng 3 2017 lúc 17:00

\(A=\frac{2012^{2013}-2012}{2011}\)

Bình luận (0)
dinhkhachoang
14 tháng 3 2017 lúc 17:04

\(A=2012+2012^2+2013^3+......+2012^{2012}\)

\(2012A=2012^2+2012^3+2012^{2013}\)

\(2012A-A=2012^{2013}-2012\)

\(2011A=2012^{2013}-2012=>A=\frac{2012^{2013}-2012}{2012}\)

Bình luận (0)
Trà My
14 tháng 3 2017 lúc 17:12

\(A=2012+2012^2+2012^3+...+2012^{2012}\)

\(2012A=2012^2+2012^3+2012^4+...+2012^{2013}\)

2012A-A=\(\left(2012^2+2012^3+2012^4+...+2012^{2013}\right)-\left(2012+2012^2+2012^3+...+2012^{2012}\right)\)

\(2011A=2012^{2013}-2012\)

\(A=\frac{2012^{2013}-2012}{2011}\)

Bình luận (0)

Các câu hỏi tương tự

Khoá học trên OLM của Đại học Sư phạm HN

Loading...

Khoá học trên OLM của Đại học Sư phạm HN